Measuring dynamic competitive relationship and intensity among the global coal importing trade. (1st December 2021) - Wang, Wenya; Fan, Liwei; Li, Zhenfu; Zhou, Peng; Chen, Xue
Highlights: The global coal import competition network is tight. Japan and China have made coal competition on the Asian-Pacific region more drastic. The competition intensity of European importers is becoming weaker. Asian countries should make out strategies to decrease the carbon dioxide emission. Abstract: Until today, the volume and trade relationships of the global coal trade still follow an increasing trend, which adversely affects both the environment and coal supply security. However, whether the possibility exists to change this trend to a decrease in global coal trade competition remains unknown. If this were possible, the volume and relationships of coal trade would gradually decrease. To address this question, this paper applies the complex network model and comprehensively explores the dynamic competitive relationship and intensity among the global coal import trade. At the global level, the results indicate that more competitive relationships regarding coal imports emerge, and the coal import competition network has changed from a core periphery structure to a reticular structure. In addition, the competitive intensity of the global coal trade continues to rise. At the regional level, the role of the Asian-Pacific region, led by Japan and China, in the evolution of this competitive pattern is increasingly becoming prominent. In contrast, the competitive intensity of European importers has declined since 2007. At the national level, Japan bore the greatest competitive pressure among all coal-importing countries from 1998 to 2007, when it was replaced by China. The intensity of competition in China has increased fiercely, from seventh in 2009 to first in 2016. Finally, based on the results, meaningful policy implications are presented. For example, it is recommended that the result of record-high levels of coal competition in Asia should receive more attention, and a more appropriate use of coal should be developed.